EXPLORING STUDENTS’ SELF-RATING PRACTICE IN WRITING CLASS: A DESCRIPTIVE QUALITATIVE STUDY AT MTSN 3 KOTA SURABAYA - Khoirun Nisa; Rakhmawati Rakhmawati; Lilik Mahmudah (TELL - US JOURNAL, 2025)
This study looks at how eighth-grade students feel about using self-rating when they write in English. The goal is to see how self-rating affects their understanding of their writing skills, their motivation, and the quality of their writing. The research uses a qualitative case study approach, where data was gathered through interviews with students from class 8D at MTsN 3 Kota Surabaya. The interviews were done online using Google Meet, and the questions were in Indonesian to make sure students understood them clearly. The results show that students mostly liked self-rating because it helped them become more aware of their strengths and weaknesses, improved their writing, and made them more motivated. But some students also mentioned problems like not knowing exactly how to evaluate their work and feeling unsure about their abilities. The study recommends including guided self-rating exercises in writing lessons to help students be more independent and reflective in their learning.